2021
DOI: 10.3233/jad-210026
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol Ameliorates Cognitive Function via Regulation of IL-33 and TREM2 Upregulation in a Murine Model of Alzheimer’s Disease

Abstract: There is a dire need for due innovative therapeutic modalities to improve outcomes of AD patients. In this study, we tested whether cannabidiol (CBD) improves outcomes in a translational model of familial AD and to investigate if CBD regulates interleukin (IL)-33 and triggering receptor expressed on myeloid cells 2 (TREM2), which are associated with improved cognitive function. CBD was administered to 5xFAD mice, which recapitulate early onset, familial AD. Behavioral tests and immunoassays were used to evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 14 publications
1
20
0
1
Order By: Relevance
“…An overall ameliorated memory and cognitive function after CBD administration was observed in studies by de Paula Faria et al and Khodadadi et al [41,47]. The latter study also concluded that the CBD-mediated improvement of cognitive abilities occurs through an enhancement of expression of IL-33 and triggering receptor expressed on myeloid cells 2 (TREM2) [47]. In a study by Wang et al CBD was demonstrated to improve lifespan and overall health span in C. elegans AD model [48].…”
Section: In Vivo Studies On Cbd In Alzheimer's Diseasementioning
confidence: 85%
See 1 more Smart Citation
“…An overall ameliorated memory and cognitive function after CBD administration was observed in studies by de Paula Faria et al and Khodadadi et al [41,47]. The latter study also concluded that the CBD-mediated improvement of cognitive abilities occurs through an enhancement of expression of IL-33 and triggering receptor expressed on myeloid cells 2 (TREM2) [47]. In a study by Wang et al CBD was demonstrated to improve lifespan and overall health span in C. elegans AD model [48].…”
Section: In Vivo Studies On Cbd In Alzheimer's Diseasementioning
confidence: 85%
“…Whereas an improvement in novel object recognition was observed in studies by Cheng et al and Coles et al [45,43]. An overall ameliorated memory and cognitive function after CBD administration was observed in studies by de Paula Faria et al and Khodadadi et al [41,47]. The latter study also concluded that the CBD-mediated improvement of cognitive abilities occurs through an enhancement of expression of IL-33 and triggering receptor expressed on myeloid cells 2 (TREM2) [47].…”
Section: In Vivo Studies On Cbd In Alzheimer's Diseasementioning
confidence: 88%
“…Surgery/anesthesia did not affect the freezing time of dNCR mice in the tone test, which is consistent with previous studies [ 16 , 20 ] and indicated that surgery/anesthesia did not impair hippocampus-independent memory. In AD mouse [ 18 , 30 ] and RNS rat [ 12 ] models, IL-33 has been proven to improve cognitive defects via anti-inflammation. Conversely, bilateral intrahippocampal injection of IL-33 (400 ng) induced IL-1β overexpression by microglia cells and cognitive impairment in mice [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that CBD may have neuroprotective effects via its impact on peroxisome proliferator-activated receptor gamma and subsequently Aβ clearance [168]. A recent translational study suggested improvements in cognition in familial AD mice with CBD due to upregulation of interleukin 33 and triggering receptors expressed on myeloid cells 2 (TREM2), which play a role in phagocytosis and reduction of inflammation associated with plaque formation [169]. Several small case series have suggested utility of dronabinol for nocturnal agitation in people with dementia [170] and for dream enactment behavior [171], but controlled trials have yet to occur.…”
Section: Cannabidiol/tetrahydrocannabinolmentioning
confidence: 99%